THE EFFECT OF TAX ARREARS BILLING BY DISTRESS WARRANT TO REPAYMENT OF TAX ARREARS - Falentino, Andre; Nawangsasi, Yuli (Jurnal ASET (Akuntansi Riset), 2014)
Abstract. The government has issued  The act No.19 of 2000 about   Billing of state tax with the  Distress Warrant  and Minister of Finance Regulation No.24 / PMK.03 / 2008 , those applicable since   February 6, 2009. This study aims to determine the effect of Tax arrears billing by Distress Warrant  to  the repayment of tax arrears on the Tax Office Pratama Bandung Cicadas. The method used is descriptive method with quantitative approach. Statistical test used is using linear regression, Pearson correlation coefficient, coefficient of determination. The hypothesis test result is that there is no effect of  Tax arrears billing by Distress Warrant to Repayment of tax arrears   The effect of Tax arrears billing by Distress Warrant to the Repayment of tax arrears is  1.02%, and  98.98% influenced by other factors such as The tax payer are appealing, to objections or Tax Repayment Installment.Keywords: tax arrears billing; distress warrant; repayment  tax arrearsAbstrak. Pemerintah menerbitkan Undang-undang No.19 tahun 2000 tentang Penagihan Pajak Negara dengan Surat Paksa dan Peraturan Menteri Keuangan No.24/PMK.03/2008 yang mulai berlaku tanggal 6 Februari 2009. Penelitian ini bertujuan untuk mengetahui pengaruh penagihan tunggakan pajak dengan surat paksa terhadap pelunasan tunggakan pajak pada Kantor Pelayanan Pajak Pratama Bandung Cicadas. Metode yang digunakan adalah metode deskriptif dengan pendekatan kuantitatif. Dari uji hipotesis diperoleh hasil bahwa pengaruh penagihan tunggakan pajak dengan surat paksa terhadap terhadap pelunasan tunggakan pajak tidak terbukti. Pengaruh penagihan tunggakan pajak dengan surat paksa terhadap pelunasan tunggakan pajak sebesar 1,02%, sedangkan sisanya yaitu sebesar 98,98% dipengaruhi oleh faktor lain seperti penanggung pajak sedang melakukan banding, mengajukan keberatan atau mengajukan permohonan angsuran dalam melakukan pelunasan tunggakan pajak.Kata Kunci: penagihan tunggakan  pajak ; pelunasan pajak ; surat paksa.